Water Resource Carrying Capacity and Coordinated Development in Yulin City of Shaanxi Province - Tao Ma; Shuangbao Han; Fucheng Li; Wenli Li; Minmin Zhao; Haixue Li (Shuitu baochi tongbao, 2023)
[Objective] The water resource carrying capacity of Yulin City, Shaanxi Province, was studied in order to provide a scientific reference for the development and utilization of water resources and regional coordinated development. [Methods] An evaluation system was constructed from the perspective of water-economy-society-ecology. Analytic hierarchy process, entropy, and TOPSIS methods were used to evaluate the carrying capacity of water resources in Yulin City. Coupled coordination degree and obstacle degree models were introduced to analyze the regional coordinated development level and the main obstacles to carrying capacity. Evolution analysis and prediction of carrying capacity were conducted based on development planning. [Results] The water resource carrying capacity indices of all districts and counties in Yulin City were at medium and weak levels, while the development of Yuyang District, Shenmu County, and Dingbian County were not coordinated. High population density and high agricultural water consumption were the main obstacles to increasing carrying capacity in Yuyang District. Ecological environment water demand was the main obstacle factor in Shenmu County. Weak water resources background, low availability, and soil erosion were the main obstacles limiting the carrying capacity of eastern counties. The overall regional water resource carrying capacity in 2020 has increased since 2016. Under future economic and social development and the implementation of water diversion projects, the water resource carrying capacity indices of Yuyang District, Shenmu County, Fugu County, and Hengshan County are expected to increase, while the water resource carrying capacity indices of other districts and counties are expected to weaken because of economic and social development and other factors. [Conclusion] Water resource carrying capacity and regional coordinated development in Yulin City are somewhat fragile and unbalanced. Therefore, it is necessary to further adjust the water use structure, optimize the allocation of water resources, and make coordinated plans to protect the water-food-safety-ecological resources.